A Meta-Analysis of Gender, Marital Status, and Residence on Condom Use Among Adults - Hariyadi, Agustin Mahardika; Putry, Mentary Febryant; Sanusi, Sita Rahayu; Murti, Bhisma; Tursina, Elsa (Journal of Maternal and Child Health, 2025)
Background: The use of condoms is the only method of contraception that can protect a person from sexually transmitted diseases (STDs). This study aims to analyze and estimate the effect of gender, marital status and residence on condom use among adults. Subject and Method: The systematic review and meta-analysis studies were conducted according to the PRISMA flowchart and PICO model. Population: Adults in general. Intervention: Gender (Female), Place of Residence (Rural) and Marital Status (Unmarried) in using condoms. Comparison: gender (male), place of residence (urban), and marital status (married). Outcome: condom use. The basic data used involves Google Scholar, PubMed, BMC, Scient Direct, and Springer Link with the keywords (“Use condom”) AND (“Gender”) AND (“Marital status”) AND (“Adult”) AND (“Cross -sectional”). Inclusion criteria were cross-sectional study articles in English published from 2014 to 2024. Data analysis was carried out using the Review Manager 5.3 application. Result: This meta-analysis included 14 cross-sectional studies from Ethiopia, Iran, Africa, and America. The sample size in this meta-analysis was 18,322. Meta-analysis showed that condom use was less in women (aOR= 0.66; 95% CI= 1.20 to 0.36; p 0.170), and more in rural areas (aOR= 0.80; 95% CI= 0.66 to 0.98; p= 0.620), with unmarried status (aOR = 0.92 CI 95%= 1.97 to 0.43; p 0.830). However, these three results were not statistically significant. Conclusion: Condom use is less among women and more in rural areas with unmarried status.